The Effects of Light Colour and Lighting Regimes on the Quail Growth and Carcass Traits - Sarica, M. (My University, 1998)
This research was carried out to determine the effects of light colours (white florescent, red and green bulb) and lighting regimes (continuous and 2L+2D intermittent lighting) on growth performances and carcass traits of japanese quails. Live weights at the age of fifth week were 151.01, 132.84 and 160.40 (P<0.05) for white, red and green colour, respectively. Quails had heavier live weights in continuous lighting regime, in general (P<0.05). The best feed efficiency was observed in the green colour light group (3.27) followed by red or white groups (3.51 and 3.63) and the differences between light colour groups were found to be statistically significant (P<0.05). In all colour groups, continuous lighting gave a better feed efficiency (P<0.05). Viability was the highest in white colour light followed by red and green light groups (97.93, 98.68 and 93.04), intermittent lighting gave a higher viability in all groups. There were significant differences between slaughter percentage of colour groups, and were 71.96%, 67.81% and 67.56% for green, white and red light, respectively.
Işık Rengi ve Aydınlatma Şeklinin Bıldırcınların Büyüme ve Karkas Özelliklerine Etkileri
Keywords: Dressing Percentage; Feed Efficiency; Light Colour; Lighting Regime; Live Weight; Quail; Viability